Growth in Children with Autosomal Recessive Polycystic Kidney Disease in the CKiD Cohort Study - Hartung, Erum A.; Dell, Katherine M.; Matheson, Matthew; Warady, Bradley A.; Furth, Susan L. (Frontiers in Pediatrics, 2016)
Background: Previous studies have suggested that some children with autosomal recessive polycystic kidney disease (ARPKD) have growth impairment out of proportion to their degree of chronic kidney disease (CKD). The objective of this study was to systematically compare growth parameters in children with ARPKD to those with other congenital causes of CKD in the Chronic Kidney Disease in Children (CKiD) prospective cohort study. Methods: Height standard deviation scores (z-scores), proportion of children with severe short stature (z-score <-1.88), rates of growth hormone use, and annual change in height z-score were analyzed in children with ARPKD (n=22) compared to two matched control groups: children with aplastic/hypoplastic/dysplastic (A/H/D) kidneys (n=44) and obstructive uropathy (OU) (n=44). Differences in baseline characteristics were tested by Wilcoxon rank sum test or Fisher’s exact test. Matched differences in annual change in height z-score were tested by Wilcoxon signed rank test. Results: Median height z-score in children with ARPKD was -1.1 [interquartile range -1.5, -0.2]; 14% of the ARPKD group had height z-score <-1.88, and 18% were using growth hormone. There were no significant differences in median height z-score, proportion with height z-score <-1.88, growth hormone use, or annual change in height z-score between the ARPKD and control groups. Conclusions: Children with ARPKD and mild-to-moderate CKD in the CKiD cohort have a high prevalence of growth abnormalities, but these are similar to children with other congenital causes of CKD. This study does not support a disease-specific effect of ARPKD on growth, at least in the subset of children with mild-to-moderate CKD.